1991
DOI: 10.1128/jb.173.13.3993-3999.1991
|View full text |Cite
|
Sign up to set email alerts
|

Common cis-acting region responsible for transcriptional regulation of Bradyrhizobium japonicum hydrogenase by nickel, oxygen, and hydrogen

Abstract: Bradyrhizobiumjaponicum expresses hydrogenase in microaerophilic free-living conditions in the presence of nickel. Plasmid-borne hup-lacZ transcriptional fusion constructs were used to study the regulation of the hydrogenase gene. The hydrogenase gene was transcriptionally induced under microaerobic conditions (0.1 to 3.0% partial pressure 02). The hydrogenase gene was not transcribed or was poorly transcribed in strictly anaerobic conditions or conditions above 3.0% 02. Hydrogen gas at levels as low as 0.1% p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

1993
1993
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 32 publications
6
55
1
Order By: Relevance
“…In free-living B. japonicum, hydrogenase activity is induced by hydrogen, low oxygen concentrations and trace amounts of nickel (Maier et al, 1978;Stults et al, 1986;van Berkum, 1987). The induced activity is caused by an increased expression of the hydrogenase structural genes (Kim et al, 1991). Our results demonstrate that HoxA is necessary to obtain increased hupSL gene expression upon induction in a microaerobic, hydrogen-containing atmosphere.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…In free-living B. japonicum, hydrogenase activity is induced by hydrogen, low oxygen concentrations and trace amounts of nickel (Maier et al, 1978;Stults et al, 1986;van Berkum, 1987). The induced activity is caused by an increased expression of the hydrogenase structural genes (Kim et al, 1991). Our results demonstrate that HoxA is necessary to obtain increased hupSL gene expression upon induction in a microaerobic, hydrogen-containing atmosphere.…”
Section: Resultsmentioning
confidence: 65%
“…Thus the hoxA gene product must be involved in positive regulation of the expression of the hydrogenase structural genes in free-living conditions. A region upstream of the hup structural genes is necessary for transcriptional regulation of hupSL gene expression by hydrogen, nickel and oxygen (Kim et al, 1991). As the predicted amino acid sequence of HoxA is characteristic for DNA-binding transcriptional regulators (Van Soom et al, 1993b), protein binding at this region was studied by means of gel retardation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we have shown that in R. capsulatus, the HupV Ϫ or Hup(UV) Ϫ mutant expressed hydrogenase at a high level, especially in the absence of H 2 . Since B. japonicum requires microaerophilic conditions to synthesize hydrogenase (19), there may be additional superimposed controls in response to oxygen, either in R. capsulatus or in B. japonicum or in both, which may explain the differences observed in the two bacteria.…”
Section: Discussionmentioning
confidence: 97%